Autophagy in mycobacterial infections: molecular mechanisms, host-pathogen interactions, and therapeutic opportunities - Li, Jinyan; Feng, Haibo; Chen, Dechun; Zhang, Huanrong; Liao, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
Mycobacteria pose significant global health burdens, with Mycobacterium tuberculosis complex causing tuberculosis-a leading infectious killer claiming over 1.25 million lives annually-and NTM driving pulmonary and ulcerative infections, particularly in immunocompromised populations. Autophagy, a conserved cellular degradation pathway, serves as a critical mechanism of host defense against mycobacteria by delivering bacteria to the lysosome. As a response, mycobacteria have evolved intricate strategies to subvert or exploit autophagy for survival. Consequently, autophagy exhibits a dichotomous role in mycobacterial infection: functioning as a protective mechanism of host while simultaneously serving as a virulence determinant hijacked by bacteria for their survival. This review synthesizes current insights into the molecular mechanisms mediating host-initiated autophagy during mycobacterial infection, as well as the bacterial strategies for subverting or hijacking autophagic pathways. While autophagy may be hijacked by mycobacteria, substantial evidence from numerous studies demonstrates that autophagy-activating agents may be beneficial in restricting mycobacteria infection, even with multidrug-resistant strains. This review also systematizes promising agents that enhance autophagy to improve bacterial clearance. By synthesizing the latest research findings, this article aims to enhance our understanding of the intricate relationship between autophagy and mycobacteria, paving the way for efficient host-directed therapies (HDTs) against this severely harmful pathogen.